Big Data, Data Analyst, and Improving the Competence of Librarian - Narendra, Albertus Pramukti (Universitas Airlangga, 2015)
Issue of Big Data was already raised by Fremont Rider, an American Librarian from Westleyan University, in 1944. He predicted that the volume of American universities collection would reach 200 million copies in 2040. As a result, it brings to fore multiple issues such as big data users, storage capacity, and the need to have data analysts. In Indonesia, data analysts is still a rare profession, and therefore urgently needed. One of its distinctive tasks is to conduct visual analyses from various data resources and also to present the result visually as interesting knowledge. It becomes science enliven by interactive visualization. In response to the issue, librarians have already been equipped with basic information management. Yet, they can see the opportunity and improve themselves as data analysts. In developed countries, it is common that librarian are also regarded as data analysts. They enhance themselves with various skills required, such as cloud computing and smart computing. In the end librarian with data analysts competency are eloquent to extract and present complex data resources as interesting and discernible knowledge.Â